2022
DOI: 10.1177/23259671211060040
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Ossification After Arthroscopic Procedures: A Scoping Review of the Literature

Abstract: Background: Heterotopic ossification (HO) is the formation of bone in soft tissue resultant from inflammatory processes. Lesion formation after arthroscopic procedures is an uncommon but challenging complication. Optimal prophylaxis and management strategies have not been clearly defined. Purpose: To present a scoping review of the pathophysiology, risk factors, diagnostic modalities, prophylaxis recommendations, and current treatment practices concerning HO after arthroscopic management of orthopaedic injurie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 85 publications
(183 reference statements)
1
4
0
Order By: Relevance
“…11,[25][26][27][28][29][30][31][32] Several studies have demonstrated that the use of NSAIDs diminishes the rate of HO after hip arthroscopy. 3,4,33 Bedi et al described an important HO rate decrease from 8.1 to 1.8% with the systematic use of NSAIDs, 11 similar to the results showed by Randelli et al, with a notable decrease from 33 to 0% after the prophylactic use of NSAIDs for 3 weeks after the arthroscopic surgery. 25 However, there is a concern regarding the use of NSAIDs due to their intrinsic side effects, especially in older patients, that can cause gastrointestinal problems, bleedings or renal alterations, and blood pressure modifications.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…11,[25][26][27][28][29][30][31][32] Several studies have demonstrated that the use of NSAIDs diminishes the rate of HO after hip arthroscopy. 3,4,33 Bedi et al described an important HO rate decrease from 8.1 to 1.8% with the systematic use of NSAIDs, 11 similar to the results showed by Randelli et al, with a notable decrease from 33 to 0% after the prophylactic use of NSAIDs for 3 weeks after the arthroscopic surgery. 25 However, there is a concern regarding the use of NSAIDs due to their intrinsic side effects, especially in older patients, that can cause gastrointestinal problems, bleedings or renal alterations, and blood pressure modifications.…”
Section: Discussionsupporting
confidence: 66%
“…HO has been observed in 0 to 44% of hip arthroscopies and 2 to 90% of total hip replacements. 1 2 3 4 5 6 7 8 9 10 While most of the patients with HO remain asymptomatic, patients with large ossifications or concomitant femoroacetabular impingement can present stiffness and discomfort, for which surgical treatment is indicated. 1 11 12 13 …”
mentioning
confidence: 99%
“…Despite the evidence for the efficacy of prophylaxis in reducing the incidence of HO, its clinical importance is still debated in the literature [ 16 , 26 , 27 ]. Kurz et al [ 12 ] in their review reported that only 25% of HO post-hip arthroscopy were symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 90% of acetabulum fractures and 8.6% of distal humerus fractures subjected to surgical treatment result in the formation of HO [ 3 ]. It can also occur after arthroscopic procedures and after hip arthroscopy was detected in up to 46% of cases [ 4 ]. Approximately 29.9% of patients with total hip arthroplasty (THA) developed HO, but most cases were asymptomatic.…”
Section: Introductionmentioning
confidence: 99%